Undiagnosed Diabetes in Kidney Transplant Candidates: A Case-Finding Strategy - Bergrem, Henrik Andreas (American Society of Nephrology, 2010)
Background and objectives: Guidelines recommend that candidates for kidney transplantation (KTx) who do not have diabetes perform a pretransplantation oral glucose tolerance test (OGTT) when fasting plasma glucose (FPG) is <110 mg/dl (<6.1 mmol/L); however, the OGTT is potentially costly and cumbersome. We studied the role of the OGTT for diagnosing diabetes and the accuracy of FPG and glycated hemoglobin (HbA(1c)) for predicting a diabetic OGTT before KTx. Design, setting, participants, & measurements: In this cross-sectional study, 889 first single-kidney transplant candidates without diabetes, mainly white, performed an OGTT during the transplantation workup. Results were studied using receiver operating characteristic analysis. Results: Of 72 (8.1%) patients with undiagnosed diabetes, only 16 (22%) had a diabetic FPG (≥126 mg/dl [≥7.0 mmol/L]). In patients with a nondiabetic FPG, diabetes (2-hour plasma glucose [2h-PG] ≥200 mg/dl [≥11.1 mmol/L]) was predicted by FPG but not by HbA(1c). Performing the OGTT in patients with FPG 92 to 125 mg/dl (5.1 to 6.9 mmol/L) identified 65 (90%) patients with diabetes (16 by FPG, 49 by 2h-PG) and required seven OGTTs per patient identified. Subjecting all patients with FPG <110 mg/dl (<6.1 mmol/L) to the OGTT identified 60 (83%) patients with diabetes (16 by FPG, 44 by 2h-PG) but required 14 OGTTs per patient. Conclusions: The OGTT was paramount in finding most cases of undiagnosed diabetes before KTx. FPG but not HbA(1c) predicted a diabetic OGTT. We suggest that white KTx candidates without diabetes perform a pretransplantation OGTT when FPG is 92 to 125 mg/dl (5.1 to 6.9 mmol/L).